(untitled) (LEARNing Landscapes, 2024)
In recent years, discourses about youth have been mired in narratives of learning loss and mental health crises. These cultural stories often pathologize youth, offering little in the way of generative pathways for educator practice to aid young people as they navigate the very real challenges in contemporary society. The experiences and reflections shared by a young man, Alberto, about the work he did with his peers and teacher demonstrates the power of community engagement, collaborative art, and responsive teaching to reframe the “problems” of education, offering new pathways to “do wellbeing” in learning spaces.